SENI TRADISIONAL DALAM SENI RUPA MODREN: ANALISIS BERDASARKAN NILAI PENDIDIKAN - Budiwirman Budiwirman; Syeilendra Syeilendra; Ary Ramadhan; Syafei Syafei (Gorga : Jurnal Seni Rupa, 2023)
Traditional arts that have high artistic value must always be preserved from extinction. In order to maintain the popularity of traditional art in Indonesia, it is necessary that artists, teachers, and society understand it deeply. Every fine arts artist, teacher, and community must have a sense of nationalism towards traditional art in order to be able to maintain and become a stronghold of traditional art itself. This study aims to rediscover the values of traditional culture that are spread in several regions in Indonesia with the hope that it can be absorbed into modern art so that the value of traditional art is not completely eroded. This research uses Spradley's qualitative research method or ethnographic qualitative research with the aim of systematically describing deeper cultural characteristics. This research produces a description of the characteristics of traditional culture contained in several traditional arts and crafts spread across Indonesia, each region has cultural characteristics that are different from other regions which are influenced by several diverse factors. The characteristics of each artistic value are maintained and absorbed into modern art for maintained and taught in the world of education so that art saviors are born who are able to transform traditional arts into modern artistic values. As art saviors, artists need awareness of a sense of "nationalism" in each of them which is obtained through an understanding of these traditional arts.Keywords: high art, education, culture, nationalism.Â AbstrakKesenian tradisional yang memiliki nilai seni tinggi harus selalu dilestarikan dari kepunahan. Untuk mempertahankan popularitas seni tradisional di Indonesia, diperlukan seniman, guru, dan masyarakat yang memahaminya secara mendalam. Setiap seniman seni rupa, guru dan masyarakat harus memiliki rasa nasionalisme terhadap seni tradisional agar mampu menjaga dan menjadi benteng kesenian tradisional itu sendiri. Penelitian ini bertujuan untuk menemukan kembali nilai nilai kebudayaan tradisional yang tersebar di dibeberapa daerah di Indonesia dengan harapan dapat dilakukan penyerapan kedalam seni modern agar nilai dari kesenian tradisional tidak terkikis sepenuhnya. Penelitian ini menggunakan metode penelitian kualitatif Spradley atau penelitian kualitatifÂ  etnografi dengan tujuan mendeskripsikan karakteristik kultural lebih mendalam secara sistematis. Penelitian ini menghasilkan deskripsi karakteristik kebudayaan tardisional yang terkandung dari beberapa kerajinan seni tradisional yang tersebar di wilayah Indonesia, setiap daerah memiliki karakterstik kebudayaan yang berbeda dari daerah lain yang dipengaruhi oleh beberapa factor yang beragam, Karakteristik dari setiap nilai kesenian dipertahankan dan diserap kedalam kesenian modern untuk dipertahankan dan diajarkan dalam dunia Pendidikan agar terlahir penyelamat kesenian yang mampu melakukan transformasi seni tradisional menjadi nilai seni modern. Sebagai penyelamat seni, seniman membutuhkan kesadaran akan rasa â€œNasionalismeâ€ pada diri masing-masing yang diperoleh melalu pemahaman akan kesenian tradisional tersebut.Kata Kunci: seni tinggi, pendidikan, budaya, nasionalisme.Â Authors:Budiwirman : Universitas Negeri PadangSyeilendra : Universitas Negeri PadangAry Ramadhan : Universitas Negeri PadangSyafei : Universitas Negeri PadangÂ References:Yoeti, O. K. (1997): Perencanaan dan Pengembangan Pariwisata.Jakarta: Pradnya Paramita.Elfachmi, A. K. (2015). Pengantar Pendidikan. Jakarta: PT Gelora Aksara Pratama.Arya Pageh, W. (2018). E-PROCEEDING The Phenomenon Of Shafe and Aesthetics Of Balinese Wayang and Cartoon Bog Bog on Bog Bog Bali Cartoon Magazine Vol. 09 Year 2010-2011.Banoe, P. (2003). Kamus Musik. Yokyakarta: Kanisius.Bentley, R. A., & O'Brien, M. J. (2017). The Acceleration of Cultural Change. From Ancestors to Algorithms: MIT Press.Berghaus, G. (1996).Â Futurism and politics: between anarchist rebellion and fascist reaction, 1909-1944. Berghahn Books.Brumm, A., Oktaviana, A. A., Burhan, B., Hakim, B., Lebe, R., Zhao, J. X., ... & Aubert, M. (2021). Oldest cave art found in Sulawesi.Â Science Advances,Â 7(3), eabd4648.Bublitz, M. G., Rank-Christman, T., Cian, L., Cortada, X., Madzharov, A., Patrick, V. M., ... & Townsend, C. (2019). Collaborative art: A transformational force within communities.Â Journal of the Association for Consumer Research,Â 4(4), 313-331.Budiwirman, B. (2018). Minangkabau Songket As a Fine Art Study. Padang: Blessing Prima.Caturwati, E. (2008). Tradisi Sebagai Tumpuan Kreatifitas Seni. Bandung: Penertbit Sunan STSI Pres Bandung.Cleaver, D. G. (1967). Linda Nochlin, Impressionism and Post-Impressionism 1874â€“1904, 222 pp. Realism and Tradition in Art 1848â€“1900, 189 pp: Englewood Cliffs, NJ: Prentice-Hall, Inc., 1966 (Sources and Documents in the History of Art series) $2.95 (paperbound).Deswarni, D., & Budiwirman, B. (2019). Meningkatkan Kemampuan Siswa Membaca Notasi Musik dengan Menggunakan Metode Demonstrasi dalam Pembelajaran Seni Musik.Â Gorga: Jurnal Seni Rupa,Â 8(2), 374-377.Dibia, I. W., & Ballinger, R. (2012).Â Balinese Dance, Drama & Music: A Guide to the Performing Arts of Bali. Tuttle Publishing.Graburn, N. H. (2021). Introduction: Arts of the fourth world Ethnic and Tourist Arts (pp. 1- 32): University of California Press.Hasbullah, H. (2009). Dasar-Dasar Ilmu Pendidikan. Jakarta: Raja Grafindo Persada.Hanurawan, F. (2016). Metode Penelitian Kualitatif Untuk Ilmu Psikologi. Jakarta: Raja Grafindo Persada.Heristian, M., Efi, A., & Budiwirman, B. (2022).Mengembangkan Karakter AnakMelaluiÂ Pembelajaran Seni Budaya.Â Gorga: Jurnal Seni Rupa,Â 11(2), 410-416.Heristian, M., Efi, A., & Budiwirman. Mengembangkan Karakter Anak Melalui Pembelajaran Seni Budaya.Â Gorga: Jurnal Seni Rupa,Â 11(2), 410-416.Huhmarniemi, M., & Jokela, T. (2020). Arctic arts with pride: Discourses on Arctic arts, culture and sustainability.Â Sustainability,Â 12(2), 604.Illahi, Mohammad Takdir. 2012. Pembelajaran Discovery Strategy dan Mental Vocational Skill. Jogjakarta: Diva Press.Ismail, D. E., Nggilu, N. M., & Tome, A. H. (2019). The Urgency of Gorontalo Traditional Cultural Regulation Expression as a Form of Legal Protection for National Culture: ICIDS.Jamalus. 1988. Panduan Pengajaran Buku Pengajaran Musik Melalui Pengalaman Musik. Jakarta: Proyek Pengembangan Lembaga Pendidikan.Johnson, R. B., & Christensen, L. (2019). Educational research: Quantitative, qualitative, and mixed approaches: Sage publications.Metusala, D., Lestari, D. A., DAMAIYANI, J., MASâ€™UDAH, S., & SETYAWAN, H. (2020). The identification of plant reliefs in the Lalitavistara story of Borobudur temple, Central Java, Indonesia. Biodiversitas Journal of Biological Diversity, 21(5).Muda, K. T., & Susanti, D. (2020). Keterancaman Lukisan Dinding Gua Prasejarah Bulu Sipong I Kabupaten Pangkep Sulawesi Selatan (Prehistoric Cave Paintings of Bulu Sipong I Kabupaten Pangkep South Sulawesi Threatened). Asian Journal of Environment, History and Heritage, 4(2).Nasrudin, N. (2017). Membaca dan menafsirkan temuan gambar Prasejarah di Pulau Misool Raja Ampat, Papua Barat. Berkala Arkeologi Sangkhakala, 18(2), 150-168.Nuruddin, A. F. M. r., Wirawan, P. E., Pantiyasa, I. W., Semara, I. M. T., & Estikowati, F. E. A. S. (2020). Cultural Heritage Tourism in Indonesia Potential of â€œGunung Gangsir Templeâ€ as a Tourist Attraction. Systematic Reviews in Pharmacy, 11(12), 283-289.O'Brien, D. (2018). Cubism: Art and Philosophy. ESPES, 7(1), 30-37.Park, S., Hwang, D., Lee, W. S., & Heo, J. (2020). Influence of nostalgia on authenticity, satisfaction, and revisit intention: The case of Jidong mural alley in Korea. International Journal of Hospitality & Tourism Administration, 21(4), 440-455.Pujiono, B., Prilosadoso, B., & Supeni, S. Alternative Media for the Preservation of Traditional ARTS Through Collaboration Pop Art Style Wayang Pacitan Beber. International Journal of Social Sciences and Humanities, 4(3), 151-159.Putra, I. D., & Abdullah, S. (2019). Diversity of Cultural Elements at The Reliefs of Pura Desa Lan Puseh in Sudaji Village, Northern Bali. Paper presented at the 5th Bandung Creative Movement International Conference on Creative Industries 2018 (5th BCM 2018).Putra, I. D. A. D. (2018). Kamasan Puppet Painting, Balinese Traditional Comics. Bandung Creative Movement (BCM) Journal, 4(1).Putra, I. D. A. D., & Abdullah, S. (2020). Early Symptoms of Modernism in Traditional Balinese Painting Began in Northern Bali. Idealogy, 5(2), 55-70.Rampley, M. (2021). 7 Readings of Modern Art: Historicism, Impressionism, Expressionism The Vienna School of Art History (pp. 141-165): Penn State University Press.Naufal, R. (2014) Pertunjukan Gendreh Pada Acara Hiburan di Kampung Cikadu Indah Kecamatan Panimbang Kabupaten Pandeglang Banten. UPI.Schulz, K., & Hayn-Leichsenring, G. U. (2017). Face attractiveness versus artistic beauty in art portraits: a behavioral study. Frontiers in psychology, 8, 2254.Sedyawati, E. (1995). Kajian Sejarah Kesenian. Jakarta: Dirjen Kebudayaan.Setiawan, A., & Handojo, A. (2017). Indonesian culture learning application based on android. Petra Christian University.Slataper, S. (2020). Futurism My Karst and My City and Other Essays (pp. 102-105): University of Toronto Press.Smith, A. (2002). Fauvism and Cultural Nationalism. Interventions, 4(1), 35-52.Soedjono, S. (2019). Fotografi Surealisme Visualisasi Estetis Citra Fantasi Imajinasi. Rekam: Jurnal Fotografi, Televisi, Animasi, 15(1), 1-12.Â Tacon, P. S. (2019). Connecting to the Ancestors: why rock art is important for Indigenous Australians and their well-being. Rock Art Research: The Journal of the Australian Rock Art Research Association (AURA), 36(1), 5-14.Thom, M. (2017). Arts entrepreneurship education in the UK and Germany: An empirical survey among lecturers in fine art. [Article]. Education and Training, 59(4), 406-426. doi: 10.1108/et-05-2016-0089.Thosibo, A., Soekamto, N., Duli, A., & Mulyadi, Y. (2019). Broken painting in the prehistoric cave and chemical content of paint used in Maros Regency, South Sulawesi. Paper presented at the Journal of Physics: Conference Series.Tompkins Lewis, M. (2007). Critical Readings in Impressionism and Post-Impressionism: An Anthology: University of California Press.Vuk, S., & Bosnar, M. (2021). Process in contemporary visual art as a paradigm shift in the visual art education: Perspective of creativity. [Article]. Creativity Studies, 14(1), 99- 111. doi: 10.3846/cs.2021.12632.